Profil Literasi Digital Siswa Kelas VIII Pada Materi Sistem Pencernaan Berbasis Augmented Reality - Dita Argarani; Muhammad Faizal Fathurrohim; Marshanti Lisbania Gratia (Departement of Mathematics Education, 2024)
Augmented reality (AR) is a technology that combines real-time computer-generated digital content with the real world. This research uses a digital literacy method adapted from Jisc (Joint Information Systems Committee). This questionnaire measures 8 indicators, namely functional skills and beyond, collaboration, critical thinking, communication, ability to find and select information, e-safety, creativity, and cultural and social understanding. The results of the research show that digital literacy among students is said to be good with a score of 2.96 and the creativity indicator shows a low score, namely 1.47.